Satu Analisis Stail Kepemimpinan Pengetua Dan Iklim Organisasi Di Sekolah Menengah Daerah Kota Setar, Kedah Darul Aman - Ahmad Rusli, Din (1997)
The focus of this research is on the principals’ leadership style and organisational climate of the teachers in Kota Setar Secondary School, Kedah Darul Aman. Three hundred and thirty respondents were chosen to carry out the research. In this research, organisational climate and demographic factors were to be related with the principals’ leadership style. Fourteen research hypotheses were developed in this research. The result has been finabed by using various analysis methods in the Statistical Package of Social Science (SPSS), including t-test, ANOVA, Correlation Analysis, Regression Analysis and Crosstab. The study showed that there is a significant correlation between organisational climate and principals' leadership style. However, there is a very small correlation between demographic factors and principals’ leadership style. T - test proved that there is no significant differences of gender on the principals’ leadership style. The result showed that organisational climate has an impact on the principals’ leadership style but very little impact on the demographic factors. Therefore there are other aspect that may contribute positive effect on excellent principals’ leadership style. Futher research can be done to identify other factors that may contribute towards excellent principals’ leadership style.